ABC of Action Learning. - Pedler, Mike (Ashgate Pub., 2011)
Reg Revans based his theories of Action Learning on 30 years of work and observation. This revised and updated reissue of the definitive text, ABC of Action Learning, is a clear, easily-read primer for anyone wishing to learn about and apply his methods. It offers a succinct, practical guide to integrating action learning into every-day situations, and enhancing the practical and managerial skills of the workforce.